Ecotourism and its effects on wildlife of Pachmarhi Biosphere Reserve - Balendra Pratap Singh; Ravi Upadhyay (African Journal of Environmental Economics and Management, 2019)
The present paper focused on ecotourism and its effects on wildlife. In the present scenario the ecotourism is a grooming sector in developing nations. However, its impact on wildlife and indigenous people has become a controversial issue. Pachmarhi Biosphere Reserve site explores the multitude of interactions that exist among the welfare of wildlife, conservation biology and socio-economy of the local people.